Ajax in action - Crane, Dave (Manning, 2006)
Val's Blog "A tremendously useful field guide specifically written for developers down in the trenches...waiting for the killer solution..." Web users are getting tired of the traditional web experience. They get frustrated losing their scroll position; they get annoyed waiting for refresh; they struggle to reorient themselves on every new page. And the list goes on. With asynchronous JavaScript and XML, known as "Ajax," you can give them a better experience. Once users have experienced an Ajax interface, they hate to go back. Ajax is new way of thinking that can result in a flowing and intuitive interaction with the user. Ajax in Action helps you implement that thinking--it explains how to distribute the application between the client and the server (hint: use a "nested MVC" design) while retaining the integrity of the system. You will learn how to ensure your app is flexible and maintainable, and how good, structured design can help avoid problems like browser incompatibilities. Along the way it helps you unlearn many old coding habits. Above all, it opens your mind to the many advantages gained by placing much of the processing in the browser. If you are a web developer who has prior experience with web technologies, this book is for you.